Changes in social value systems. The basis of a cultural theory of social change - Słaboń, Andrzej (Journal of Public Governance, 2017)
The aim of the paper is to formulate a cultural theory of social changes. The author analyzes the process of change in the sphere of values, which are the main component of culture. A value is defined as validity. Changes in the sphere of values occur not only in the vertical but also in the horizontal dimension (shifts between the centre and peripheries). The author distinguishes several types of value systems that are characteristic of the Polish society: traditional, post-traditional, universalistic, success-oriented, consumption-driven, and rebellious. Changes in the sphere of values occur when the degree of coherence of each of the systems rises or when the systems interact (e.g. during a “war of cultures”). Changes of social values can also be the result of compensational processes in response to dominating characteristics of social reality.